Protective effects of vitamin D3 (cholecalciferol) on vancomycin-induced oxidative nephrotoxic damage in rats - Rouba Yasser Al-Sroji; Shaza Al-Laham; Ahmad Almandili (Taylor & Francis Group, 2023)
AbstractContext Vancomycin (VCM), an important antibiotic against refractory infections, has been used to treat secondary infections in severe COVID-19 patients. Regrettably, VCM treatment has been associated with nephrotoxicity. Vitamin D3 can prevent nephrotoxicity through its antioxidant effect.Objective This study tests the antioxidant effect of vitamin D3 in the prevention of VCM-induced nephrotoxicity.Materials and methods Wistar Albino rats (21) were randomly divided into 3 groups: (A) control; (B) VCM 300 mg/kg daily for 1 week; and (C) VCM plus vitamin D3 500 IU/kg daily for 2 weeks. All the rats were sacrificed and serum was separated to determine kidney function parameters. Their kidneys were also dissected for histological examination and for oxidative stress markers.Results Lipid peroxidation, creatinine, and urea levels decreased significantly (p < 0.0001) in the vitamin D3-treated group (14.46, 84.11, 36.17%, respectively) compared to the VCM group that was given VCM (MIC<2 μg/mL) only. A significant increase was observed in superoxide dismutase levels in the vitamin D3-treated group (p < 0.05) compared to rats without treatment. Furthermore, kidney histopathology of the rats treated with vitamin D3 showed that dilatation, vacuolization and necrosis tubules decreased significantly (p < 0.05) compared with those in the VCM group. Glomerular injury, hyaline dystrophy, and inflammation improved significantly in the vitamin D3 group (p < 0.001, p < 0.05, p < 0.05, respectively) compared with the VCM group.Discussion and conclusions Vitamin D3 can prevent VCM nephrotoxicity. Therefore, the appropriate dose of this vitamin must be determined, especially for those infected with COVID-19 and receiving VCM, to manage their secondary infections.